Pengaruh Angka Harapan Hidup, Rata-Rata Lama Sekolah, dan Jumlah Angkatan Kerja terhadap Produk Domestik Regional Bruto Istimewa Yogyakarta (2017-2023) - Anshori, Wakhid Zulkifli; Winarti, Asih Sri; Wijayanti, Diah Lufti (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2025)
This study aims to analyze the impact of life expectancy, average years of schooling, and labour force on the Gross Regional Domestic Product (GRDP). This research utilizes secondary data, including GRDP at constant prices, Life Expectancy (LE), Average Years of Schooling (AYS), and Labor Force in the Regencies/Cities of the Special Region of Yogyakarta from 2017 to 2023, as published on the bps.go.id website. The study employs a sample of five regencies/cities from 2017–2023. The analysis method used in this research is panel data regression analysis, conducted using Stata 17 software. The findings indicate that life expectancy, average years of schooling, and the labor force positively and significantly influence the Gross Regional Domestic Product (GRDP) in the Regencies/Cities of the Special Region of Yogyakarta from 2017 to 2023. Keywords: Life Expectancy, Average Years of Schooling, Labor Force, Gross Regional Domestic Product, Panel Data Regression